2015
DOI: 10.1002/ijc.29462
|View full text |Cite
|
Sign up to set email alerts
|

Risk of second primary malignancies in women with breast cancer: Results from the European prospective investigation into cancer and nutrition (EPIC)

Abstract: Women with a diagnosis of breast cancer are at increased risk of second primary cancers, and the identification of risk factors for the latter may have clinical implications. We have followed‐up for 11 years 10,045 women with invasive breast cancer from a European cohort, and identified 492 second primary cancers, including 140 contralateral breast cancers. Expected and observed cases and Standardized Incidence Ratios (SIR) were estimated using Aalen‐Johansen Markovian methods. Information on various risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
76
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 23 publications
6
76
2
Order By: Relevance
“…The SIRs were even higher in premenopausal women (point estimates of SIR were 1.8 and 2.0, but 95%CIs were not reported). In the European Prospective Investigation into Cancer and Nutrition [19], Ricceri et al found an increased risk of colorectal cancer (SIR = 1.71, 95%CI 1.43, 2.00) after diagnosis of breast cancer. In a nested case-control study using SEER data, Kmet et al [37] observed a twofold increase in the risk of colon cancer among breast cancer patients who had either a family history of breast cancer or a high body mass index.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SIRs were even higher in premenopausal women (point estimates of SIR were 1.8 and 2.0, but 95%CIs were not reported). In the European Prospective Investigation into Cancer and Nutrition [19], Ricceri et al found an increased risk of colorectal cancer (SIR = 1.71, 95%CI 1.43, 2.00) after diagnosis of breast cancer. In a nested case-control study using SEER data, Kmet et al [37] observed a twofold increase in the risk of colon cancer among breast cancer patients who had either a family history of breast cancer or a high body mass index.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have explored the risk of colorectal cancer after a breast cancer diagnosis and treatment, and the results have been inconsistent [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…21 22 Hormonal treatment of a primary breast cancer increases the risk for endometrial, gastric, colon and ovarian cancers with an excess risk for endometrial cancer observed especially after tamoxifen therapy. 22 Reproductive/hormonal and genetic factors (eg, BRCA1, BRCA2) as well as obesity are recognised as common risk factors for multiple primaries (table 3). 23 For the breast cancer genes BRCA1 and BRCA2, there is a strong association with an increased risk for a second breast or ovarian cancer.…”
Section: Multiple Primaries In Female Patients With Breast Cancermentioning
confidence: 99%
“…9 The risk of a second breast, endometrial or ovarian cancer after breast cancer is inversely associated with postmenopausal status and history of full-term pregnancy. 22 Late toxic effects of radiotherapy and chemotherapy also contribute to the increased risk for a secondary primary tumour after breast cancer. Acute myeloid leukaemia (AML) can be induced during the first 2 years after radiotherapy and is a late effect of adjuvant chemotherapy.…”
Section: Multiple Primaries In Female Patients With Breast Cancermentioning
confidence: 99%
“…Breast cancer ranks as the second cause of cancer death among women (1)(2)(3)(4). Clinical cases have indicated that most of the breast cancer deaths are caused by metastasis (5,6), and as a distinct metastatic pattern, breast cancer cells are more inclined to migrate into lymph nodes, bone marrow, lung, liver and brain (7).…”
Section: Introductionmentioning
confidence: 99%